Preparation and Electrochemical Performance of V2O5 @N-CNT/S Composite Cathode Materials - Liu, Cheng; Xiang, Meng; Zhang, Haiyang; Feng, Shuaiqiang; Xiao, Jianrong; Ma, Songshan; Li, Xinyu (Frontiers in Energy Research, 2021)
Lithium–sulfur battery has received widespread attention because of its high energy density, low cost, environmental friendliness, and nontoxicity. However, the insulating properties of elemental sulfur, huge volume changes, and dissolution of polysulfides in electrolytes that result in the shuttle effect, low sulfur utilization, and low rate performance seriously hinder the commercialization of lithium–sulfur batteries. In this work, a composite material of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) and V2O5 was designed and fabricated to serve as the positive electrode of lithium–sulfur battery via the hydrothermal method. The positive electrode of the V2O5@N-CNTs composite material could reach an initial discharge specific capacity of 1453 mAh.g−1 at a rate of 0.1 C. Moreover, the composite material could maintain a discharge ratio of 538mAh.g−1 at a rate of 0.5 C even after 200 charge and discharge cycles. After 400 cycles, the composite had a specific discharge capacity of 492 mAh.g−1 at a rate of 1.0 C. The excellent electrochemical performance of the V2O5@N-CNT/S composite cathode material was due to the fact that V2O5 contains oxygen ions and has a strong polarized surface. Furthermore, nitrogen doping changed the hybrid structure of carbon atoms and provided additional active sites, thereby improving the conductivity of the material itself and effectively inhibiting the dissolution and diffusion of polysulfides.